HUMANITY IN THE ENFORCEMENT OF ANTI-CORRUPTION LAWS - Michael, Tomy (Jurnal Hukum Bisnis Bonum Commune, 2019)
The justice of the law in the context of the law always subjected to refraction meaning. The justice of law can’t be interpreted as specific but can be shown through deeds. The justice of the law which is considered better by most people not necessarily also have the same feeling with the justice of the law. There are various dimensions to distinguish it. In the context of the state, the leader is the main pedestal of enforcing the law on the laws and regulations in there. When the leader of a country is it where it as full support to the state institutions that overcome the problems of corruption, namely the Corruption Eradication Commission and the whole thing can run optimally. Advice taken, namely by forming laws and regulations based on humanity with other humans, namely the variation of the judgment. The judgment referred to is social work, exile to the island of the smallest, lethal injection and impoverishment through from the first of assets appropriately. Thus, humanity in enforcing anti-corruption laws can be run better by paying attention to the humanity of the injured party.